Mechanism and Numerical Simulation of Vertical Fracture Propagation in Composite Coal Rock - Fan Zhang; Hanjin Wan; Yan Liu; Shuwei Li; Zijiang Li (Shock and Vibration, 2022)
Vertical fracture propagation mechanism is important to understand the effect of hydraulic fracturing on the roof of outburst coal seams. In this paper, the differences in physical parameters and in situ stress between an outburst coal seam and its roof strata were compared, and influencing factors of roof-fracturing fractures connecting coal seams were vertically analyzed. The impact of different fracturing strata and injection rates on fracture propagation was studied by numerical models. Results show that the horizontal principal stress of an outburst coal seam is less than that of roof strata, and the fracture length of roof fracturing is larger than that of an outburst coal seam. Roof-fracturing fracture of an outburst coal seam has the material conditions to communicate downward with the coal seam. The downward propagation height of roof-fracturing fracture is positively correlated with the minimum horizontal stress difference between an outburst coal seam and its roof strata. Soft coal fracturing cannot form a long fracture dominated by tensile failure, so the coal seam can be communicated by transforming the roof strata of soft coal to form vertical fractures. The injection rate affects the failure location, fracture width, and fracture-propagation path of the numerical model. Construction parameters should be reasonably designed in accordance with the physical parameters of coal and rock, construction displacement, and in situ stress. These research results can provide a theoretical basis and data support for the design, and optimization of construction parameters of roof fracturing in outburst coal seams.